Anisotropy of Core-collapse Supernovae Effected by the Disks of Active Galactic Nuclei - Jiao-Zhen She; Tong Liu; Bao-Quan Huang; Yun-Feng Wei; Fu-Lin Li; Jin-Jun Geng; Xue-Feng Wu (The Astrophysical Journal)
Active galactic nuclei (AGN) disks provide dense environments that influence star formation, evolution, and migration. In AGN disks, pressure gradients and migration accelerations could create the anisotropy of the core-collapse supernovae that occurs when massive stars explode at the end of their lives. In this study, we construct equilibrium equations by considering these two factors and then compute the light curves for three types of progenitor stars at different locations of AGN disks for different supermassive black hole (SMBH) masses, accretion efficiencies, explosion energies, and masses of ejecta. The results show that the migration acceleration has more significant effects on the anisotropic explosions than the pressure gradients of the AGN disks. The anisotropic luminosities are pronounced at large radii, and massive SMBHs would suppress the anisotropy and reduce the total luminosity.